Soil carbon and nitrogen changes in long-term continuous lowland rice cropping - Pampolino, Mirasol F.; Laureles, Eufrocino V.; Gines, Hermenegildo C.; Buresh, Roland J. (Wiley, 2008)
Rice (Oryza sativa L.), the main staple food in Asia, is typically produced on submerged anaerobic soils, which generally have slower decomposition of soil organic matter (SOM) than aerobic soils. We sampled four long‐term experiments in the Philippines, with two or three rice crops grown each year with continuous or near‐continuous soil submergence, to determine the effect of fertilizer management on long‐term changes in soil C and N and on C and N balances. Soils were an Aquandic Epiaquoll, an Entic Pellustert, and a Typic Pelludert; soil pH ranged from 5.9 to 6.7. After 17 to 21 yr of continuous rice cultivation, the concentration of total soil organic C (SOC) and total soil N (NT) in the topsoil (0–20 cm) were greater with N–P–K fertilization than without fertilization. During 15 yr of additional continuous rice cropping, topsoil SOC and NT were consistently maintained or increased regardless of N–P–K fertilizer regime. Topsoil SOC increased up to 10% in an experiment with three rice crops per year and removal of all aboveground plant biomass after each crop. Subsoil SOC and NT (20–80 cm) were not affected by fertilization. The N balances indicated that biological N2 fixation averaged 19 to 44 kg N ha−1crop−1 across the four experiments. Anaerobic N mineralization (ANM) in the topsoil was maintained during 15 yr of continuous rice cropping with N–P–K fertilization in all four experiments. The results suggest that continuous cultivation of irrigated rice with balanced fertilization on submerged soils maintained or slightly increased SOM and maintained soil N‐supplying capacity.